Roasted Astragalus membranaceus Inhibits Aβ25–35-Induced Oxidative Stress in Neuronal Cells by Activating the Nrf2/HO-1 and AKT/CREB/BDNF Pathways - Yun-Jeong Ji; Min Hye Kang; Sin Hee Han; Geum-Soog Kim; Hyung Don Kim; Gwi Yeong Jang (Antioxidants)
(1) Background: Astragalus membranaceus (AM) has antioxidant and anti-inflammatory effects, but its specific mechanism of action in the brain is still unclear. In this study, we developed a roasting process to maximize the cognitive improvement impact of AM. We focused on enhancing physiological activity to enhance the brain neuron protection effect and alleviate neuronal damage caused by neurodegenerative diseases. (2) Methods: AM was roasted at 260 °C for 20, 30, or 40 min, and the hot water extracts were tested on HT22 cells for ROS levels, apoptosis, and antioxidant protein expression. The effect on the BDNF-AKT-CREB pathway under stress was also analyzed. (3) Results: Roasted AM decreased ROS production and the expression of apoptosis-related factors while activating the expression of antioxidant proteins in HT22 cells treated with Aβ25–35. In particular, 30 min roasting (R-AM2) significantly reduced ROS production, inhibited cell death, and increased antioxidant protein expression. The Nrf2 pathway was activated Bax, and cleaved caspase-3 levels were reduced. BDNF and p-CREB expression were increased by 20% and 50–70%, respectively. In the MAPK pathway, p-ERK levels were increased by 30%, and p-P38 levels were increased by approximately 20%. (4) Conclusions: These findings suggest that roasted AM upregulates brain-derived neurotrophic factor (BDNF) in HT22 cells, providing neuroprotective effects by activating the AKT/CREB/BDNF pathway and inhibiting neuronal apoptosis. Therefore, roasted AM shows potential as a neuroprotective agent for preventing or treating neurodegenerative diseases, such as Alzheimer’s, linked to BDNF deficiency.